Composting a Mixture of Cactus Pear Pruning Waste and Spent Coffee Grounds: The Chemical Evaluation of Organic Fertilizer in Response to Basil Quality and Growth - Paolo Roberto Di Palma; Giulio Gazzola; Silvia Procacci; Oliviero Maccioni; Maria Rita Montereali; Valentina Tolaini; Margherita Canditelli; Loretta Bacchetta (Horticulturae, 2025)
In specialized orchards, approximately 6–10 tons/hectare of cactus pear pruning waste and 60 million tons of spent coffee grounds are estimated to be produced each year worldwide. Composting is a process that produces stable organic matter useful in agriculture. The aim of this work was to explore the potential of Opuntia ficus-indica (OFI) cladodes and spent coffee ground (SCG) mixtures for compost production and to assess their benefits for agricultural applications. Three composting campaigns were carried out using rotating composters. Feedstock for these campaigns was formulated with different ratios of OFI and SCGs, and the compost obtained were characterized by their chemical and physical proprieties. To assess these composts, basil was grown in plots using growing substrate as a blank and comparing it with substrate mixed with 10% of each compost. All plants sprouted and grew up. While no significant differences were detected in polyphenol content among the grown plants, the yields with compost at OFI–SCG (3.3:1) were differentiated for longer shoots and there was greater biomass compared to the control. Compost obtained from cladode mixed with spent coffee grounds proved to be a good soil improver with the characteristics of being able to ameliorate soil fertility and plant growth.